(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How can companies effectively communicate their value to target groups through clear messaging, channel integration and active audience engagement? Purpose: The aim of the research is to identify strategies and approaches that enable clear articulation of companies’ offered value and to explore opportunities for improving communication through the EFQM 2020 model. Method: The qualitative part of the research includes a case study analysis of successful business practices. Results: The study highlights the importance of clear value definition, personalized and consistent communication, and persuasive value selling for business competitiveness. The EFQM 2020 model provides a framework for enhancing these processes. Organization: The research has practical significance for managers, offering guidelines for improving communication strategies. Society: The study contributes to corporate social responsibility by encouraging transparent and ethical communication that considers consumer needs. It also emphasizes the importance of environmentally friendly practices in shaping offered value. Originality: The research is innovative as it links effective communication with the theoretical principles of the EFQM excellence model. Its value lies in practical recommendations for applying this model to improve communication processes. Limitations/Future Research: The study is limited to selected sectors and specific companies, restricting the generalization of findings. Further research could include a broader range of industries and examine the long-term effects of using the EFQM model on various aspects of communication.